Validating consensus-defined severity grading of lymphatic complications after kidney transplant - Sabagh, Mohammad Sadegh; Mohammadi, Sara; Ramouz, Ali; Khajeh, Elias; Ghamarnejad, Omid; Morath, Christian; Mieth, Markus; Kulu, Yakup; Zeier, Martin; Mehrabi, Arianeb; Golriz, Mohammad (Journal of Clinical Medicine, 2021)
Lymphatic complications after kidney transplantation (KTx) are associated with morbidities such as impaired wound healing, thrombosis, and organ failure. Recently, a consensus regarding the definition and severity grading of lymphoceles has been suggested. The aim of the present study was to validate this classification method. All adult patients who underwent KTx between December 2011 and September 2016 in our department were evaluated regarding lymphoceles that were diagnosed within 6 months after KTx based on the recent definition. Patients with lymphoceles were categorized according to the classification criteria, and clinical outcomes were compared between the groups. In our department, a total of 587 patients underwent KTx between 2011 and 2016. Lymphoceles were detected after KTx in 90 patients (15.3%). Among these patients, 24 (26.6%) had grade A lymphoceles, 14 (15.6%) had grade B, and 52 (57.8%) had grade C. The median duration times of intermediate care (IMC) and hospital stay were significantly higher among patients with grade C lymphoceles than they were among patients with grade A and B lymphoceles. Significantly more patients with grade C lymphoceles were readmitted to the hospital for treatment. The recently published definition and severity grading of lymphoceles after KTx is an easy-to-use and valid classification system, which may facilitate the comparison of results from different studies on lymphoceles after KTx.
Gesehen am 15.12.2021